Ratio analysis of twitter social media accounts for qualitative research using the explorative method - I Nyoman Hendra Laksmana; I Putu Hendika Permana (Jurnal Mantik, 2023)
Social Media is an online medium that is used by one another where users can easily participate, communicate, and interact without being limited by space and time. One application that is often used is Twitter. Twitter is a social media application that provides a space to communicate with anyone without usage limits. This research was conducted to find the ratios contained in Twitter social media accounts. The research method used is an explorative method to find the variables contained in Twitter. These variables will then be compared to be tested for relevance to find the relevant ratio. These ratios can later be used to perform analysis that can be measured mathematically so that they can be used to assess the performance of a Twitter account. The results of this Twitter social media research show that there are 33 relevant ratios for assessing, measuring, and comparing the credibility of a Twitter account.